Corrosion fatigue crack growth mechanisms in offshore monopile steel weldments - Adedipe, Oyewole; Brennan, Feargal P.; Mehmanparast, Ali; Kolios, Athanasios; Tavares, Isaac (Wiley, 2017)
Offshore structures are generally fabricated of welded joints, which are considered as potential spots for crack initiation owing to the degree of stress concentrations imposed by the weld geometry and the effects of residual stresses introduced by welding processes. There are significant numbers of the current and anticipated offshore installations coupled with the use of newer materials and fabrication techniques. It is therefore important to understand the crack growth mechanisms in these structures accompanied with the effects of mean or residual stresses for a safe estimation of their service lives. In this paper, crack growth results of HAZ and weld materials similar to those used for offshore installations are presented. Tests were conducted in air and in simulated free-corrosion conditions at loading frequencies of 0.3 Hz in seawater, 5 Hz in air and at loading ratios of 0.1, 0.5 and 0.7. Results showed that crack growth rates were influenced by mean stresses, materials microstructure accompanied by welding procedure and environment. Crack growth results showed good agreement when compared with those obtained from other steels used for offshore structures.
Keywords: Crack growth rates; HAZ; Free-corrosion; Weld; Mean stress